Estudo de composição para concreto extrudável para pré fabricados - Quevedo, Valéria Ramos Baltazar (2013)
A well established and widely used in the industries of ceramics and polymers, the extrusion process has been also explored by the concrete industry. Although the industry of prefabricated structural concrete using superplasticizers, there are still no specific tests to characterize the behavior in the fresh concrete used for extrusion. Although the industry prefabricated concrete structural use superplasticizers, there're not no specific tests to characterize the behavior of the fresh concrete used for extrusion. It was observed that, even in large companies, the evaluation consists of the slump test in truncated cone and the intuitive experience of an employee to handle the concrete with a shovel manual. However the concrete cast in molds is done by extruding machines that have greater strength and consistency in application. Thus extrudability of concrete is based on the testing of "slump test" and the personal evaluation of the operator, being confirmed in a pilot batch in industrial process itself. This work was based on the manufacturing process of extruded tiles freestanding. Aiming to simulate some of the conditions of the production process, there was an adaptation of the test box-L, which was inserted in the reservoir hose vibrator housing. The test consisted in assessing the behavior of the concrete to be inserted into the reservoir from the L-box and immediately after opening the gate, with and without prior vibration of concrete in the tank, so as to better define a test procedure. For a rheological analysis was proposed to carry out squeeze flow test conducted with concrete mortar and concrete strength for extrusion. We used the same settings as used for the test mortar testing machine universal type, load cell 2000 N, and sample top plate, both 10 cm in diameter, free deformation, and the punch diameter equal to the diameter sample. Assays for adjusting the height of the sample (5 cm) were made in order to avoid that instead of being deformed by the compressive shear occur in the gravel. Was performed characterization of raw materials and compression testing which determined the best ratio between the fine sand natural, artificial sand and gravel in the following proportions: 25%: 25%: 50% to 0%: 50%: 50% by mass. For each of these ratios were determined for concrete compositions with values of "m" ranging from 4.0, 4.5 and 5.0, which reduces the amount of cement up to 16%. We used superplasticizer 3rd generation based Polycarboxylate. To set the content of admixture slump test was performed test, the industry benchmark for the choice of composition, thereby setting the 16 estudo.Para compositions for each of these ratios were determined for concrete compositions with values of "m" varying from 4.0, 4.5 and 5.0, which reduces the amount of cement up to 16%. We used superplasticizer 3rd generation based Polycarboxylate. The main test possible to create a methodology to assess the behavior of concrete on vibration, providing information such as: appearance, cohesion, thixotropy and flow profile. This can make adjustments allow real concrete workability based on the characteristics of the production process and extruded profile part. The rheological analysis verified that the flow conditions experienced by the cement is not retained in the concrete, especially in regard to cohesion and adhesion. Other factors were also observed, such as segregation, exudation and behavior over time. The results show that significant differences occur, and some features disclosed in the mortar on the concrete not reproduced. Testing of mechanical strength showed that all compositions meet the minimum standards set out in and about the workability was observed that the compositions only with artificial sand showed a lack of cohesion noticeable slump test. Set up the test L-box pre adapted as best vibration test procedure. The results showed that even compositions with zero rebate which would be discarded by the industry had flowed workability and vibration, and the admixture levels and influence the time profile of the flow.